(untitled) (Malaysian Journal of Learning and Instruction, 2024)
Purpose – Given the research gaps identified in a literature review, this study aims to uncover how the intensity of learners’ motivational behavior and its predictors vary with grade level. Methodology – A large-scale survey was conducted to examine motivational behavior and its predictors among EFL learners across three education levels and ten grades in Taiwan: primary school (Grades 3 to 6), junior high school (Grades 7 to 9), and senior high school (Grades 10 to 12). A total of 12,441 valid cases were collected from both rural and urban areas in Taiwan. ANOVA and multiple regression analysis were used to analyze the data. Findings – The results showed a significant effect of grade level on the intensity of motivational behavior. Specifically, learners’ intensity of motivational behavior tended to decline with grade level (years of study). The significant predictors of motivational behavior also differed with grade level. Significance – In addition to theoretical and methodological contributions to L2 motivation research, this study can enhance understanding of factors that could enhance learners’ motivational behavior and offer implications to assist EFL teachers in developing motivational teaching strategies.